Response to treatment in Brazilian patients with chronic hepatitis C is associated with a single-nucleotide polymorphism near the interleukin-28B gene - Grandi, Tarciana (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
A single-nucleotide polymorphism (SNP) upstream of interleukin (IL)28B was recently identified as an important predictor of the outcome of chronic hepatitis C patients treated with pegylated interferon plus ribavirin (PEG-IFN/RBV). The aim of this study was to investigate the association between the IL28B gene polymorphism (rs12979860) and virological response in chronic hepatitis C patients. Brazilian patients (n = 263) who were infected with hepatitis C virus (HCV) genotype 1 and were receiving PEG-IFN/RBV were genotyped. Early virological response (EVR) (12 weeks), end-of-treatment response (EOTR) (48 weeks), sustained virological response (SVR) (72 weeks) and relapse were evaluated using conventional and quantitative polymerase chain reaction (PCR) assays. The frequency of the C allele in the population was 39%. Overall, 43% of patients experienced SVR. The IL28B CC genotype was significantly associated with higher treatment response rates and a lower relapse rate compared to the other genotypes [84% vs. 58% EVR, 92% vs. 63% EOTR, 76% vs. 38% SVR and 17% vs. 40% relapse rate in CC vs. other genotypes (CT and TT), respectively]. Thus, the IL28B genotype appears to be a strong predictor of SVR following PEG-IFN/RBV therapy in treatment-naïve Brazilian patients infected with HCV genotype 1. This study, together with similar research examining other SNPs, should help to define adequate protocols for the treatment of patients infected with HCV genotype 1, especially those with a poor prognosis.